Necesidad de garantizar en el sistema penitenciario el tratamiento de las personas privadas de libertad, con miras a su rehabilitación y reinserción social - Calderón Serrano, Juan Eduardo (2014)
The Art. 201 of the Constitution of the Republic of Ecuador requires that the system of social rehabilitation will aim the comprehensive rehabilitation of persons convicted criminally for reintegration into society and the protection of detainees and ensuring their rights. Consideration should be given to prisoners, having been lawbreakers, they have during their internment opportunity to show society, a change in their behavior and moral behavior; hence it is the responsibility of the Ecuadorian prison system the deliver to society rehabilitated persons in its entirety, which is why I propose this project beyond being feasible is real, by the application of labor and mandatory study deprived of freedom throughout the time of their detention, accompanied by individual and group psychologies therapies; that is to be created and implemented a Code of Ethics and Procedural Manual for Freedom and other private for prison staff working in detention centers. The Art Integral 701 of the Organic Code of Criminal Procedure states that: "The treatment of persons deprived of their liberty with a view to their rehabilitation and reintegration into society, is based on the following areas: 1 Labor 2 Education, Culture and Sports 3 Health 6 4. Family and Social Bonding 5. Reintegration The development of each of these lines of treatment is determined by the regulations of the National Social Rehabilitation." As for the labor system need state support for their reintegration, as the National Development Bank credit spreads on those convicted or rehabilitation centers in the country propose forming micro, woodworking, metalworking, seamstress and beauty with order to achieve a true social rehabilitation. It is necessary to amend the Code of Execution of Sentences and Social Rehabilitation; incorporating a Code of Ethics or a procedure manual for prison officials and private freedom, around the structural reality of Prisons, the types of crimes committed by the inmates and the effect caused to society by private of freedom. It is necessary that the State, work towards preventing the commission of the crime and its fatal consequences; and the reparation to the victim of crime. While it is true in recent years the current regime has built new places of deprivation of liberty zonal, to combat overcrowding; but it has been working to change this grim reality, as is all the mandatory application of the work and study of prisoners; is much to be done as it is not working on attacking the offense inside and outside prison walls.